Dietary Fibres: Their Analysis in Animal Feeding, and Their Role in Rabbit Nutrition and Health - Thierry Gidenne (Indonesian Center for Animal Research and Development, 2013)
Two centuries ago Heinrich Einhof developed the so-called Weende method (crude fibre), to first deals with the fibre content of the feeds for ruminants, and proposes to isolate a residue called the